2005
DOI: 10.1128/jcm.43.9.4713-4718.2005
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of and Screening for Cytomegalovirus Infection in Pregnant Women

Abstract: No single diagnostic test for cytomegalovirus (CMV) infection is currently available for pregnant women at all stages of gestation. Improved accuracy in estimating the timing of primary infections can be used to identify women at higher risk of giving birth to congenitally infected infants. A diagnostic algorithm utilizing immunoglobulin G (IgG), IgM, and IgG avidity was used to prospectively screen serum from 600 pregnant women enrolled from two groups: <20 weeks gestation (n ‫؍‬ 396) or >20 weeks gestation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
127
4
11

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 161 publications
(152 citation statements)
references
References 56 publications
10
127
4
11
Order By: Relevance
“…The current study had demonstrated that HCMV infection in pregnant women with spontaneous abortion was 36%, this result is comparable with result of a study done in Erbil city, which found that the seropositivity was 30.05% (18) . However, other studies showed higher rate than result of present study, which reported a detection rates ranged between 62.3% and 81.1% (19,20) . When compare to studies conducted in Arabic countries such as Tunisia, where a 96.3% seroprevalence of HCMV antibody was reported among 404 Tunisian pregnant women (21) .…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The current study had demonstrated that HCMV infection in pregnant women with spontaneous abortion was 36%, this result is comparable with result of a study done in Erbil city, which found that the seropositivity was 30.05% (18) . However, other studies showed higher rate than result of present study, which reported a detection rates ranged between 62.3% and 81.1% (19,20) . When compare to studies conducted in Arabic countries such as Tunisia, where a 96.3% seroprevalence of HCMV antibody was reported among 404 Tunisian pregnant women (21) .…”
Section: Discussioncontrasting
confidence: 54%
“…Human cytomegalovirus is found universally throughout all geographic locations and in all socioeconomic groups (19) . Also, this result agrees with Pechaham et al 2001 (29) .…”
Section: Discussionmentioning
confidence: 99%
“…IgG prevalence is between 40% to 100%; while IgM seroprevalence rate is between 0% to 10%, depending on the variability of viral accessibility and its circulation rate in the community (Ray and Mahajan,1997;Mustakangas et al, 2000;Turbadkar et al, 2000;Brooks et al, 2001;Munro et al, 2005). As previously mentioned, our study indicated that IgG seroprevalence rate was 93.0 % that is comparable with those of developing countries (90% -100%) (Brooks et al, 2001;Munro et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…IgG prevalence is between 40% to 100%; while IgM seroprevalence rate is between 0% to 10%, depending on the variability of viral accessibility and its circulation rate in the community (Ray and Mahajan,1997;Mustakangas et al, 2000;Turbadkar et al, 2000;Brooks et al, 2001;Munro et al, 2005). As previously mentioned, our study indicated that IgG seroprevalence rate was 93.0 % that is comparable with those of developing countries (90% -100%) (Brooks et al, 2001;Munro et al, 2005). In contrast, IgM seroprevalence rate 5.4% is very close to that reported in developed countries (3%-5.5%) (Ray and Mahajan,1997;Mustakangas et al, 2000;Turbadkar et al, 2000;Munro et al, 2005).These findings indicated the fact that by the age of 44 almost 93% of women had encountered hCMV, while active infection due to viral circulation occurred in 5.4% of the cases during child-bearing age.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with T cell immunodeficiency particularly fetus, preterm neonates, transplant receivers as well as HIV infected patients are at a higher risk of CMV infection. This virus is the most common factor for congenital and prenatal infections (5)(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%